The Association Between Sociability and COVID-19 Pandemic Stress - Luo, Peihao; LaPalme, Matthew L.; Cipriano, Christina; Brackett, Marc A. (Frontiers in Psychology, 2022)
The COVID-19 pandemic threatened our physical health, alongside our mental and social well-being. Social distancing requirements, which are necessary to mitigate the spread of COVID-19, increased social isolation by limiting social interactions that are an essential part of human well-being. In this study, we examined the stress caused by COVID-19 early on in the pandemic through the lens of individual preference for social interaction (PSI) among a large sample of preservice educators (N = 2,183). We found that individuals vary in their PSI, including deriving joy from social interactions and using social support to manage emotions. Our study showed that individuals who have greater PSI experienced greater COVID-19 stress. This study also contributed to prior literature which has sought to relate pandemic-related stress to demographic group differences. We found no significant relationship between demographic membership (gender, race, and sexual orientation) and COVID-19 stress. This study is among the first, however, to demonstrate that vulnerability to pandemic stress varies as a function of PSI. Implications of these findings in understanding how COVID-19 stress might interact with individual differences such as sociability and need for affiliation, including ways people can better cope with pandemic isolation are discussed.